Mycoplasma pneumoniae-Associated Encephalitis: Favorable Aggressive Immunosuppression in a Patient - Della Giustina, Elvio; Bergonzini, Patrizia; Sintini, Michele; Spagnoli, Carlotta; Fusco, Carlo; Salviato, Tiziana; Reggiani Bonetti, Luca (Journal of Pediatric Neurology, 2024)
Meningoencephalitis is the most important extrapulmonary manifestation of Mycoplasma pneumoniae infection. It is complicated by seizures in at least 40% of cases, and in half of them, status epilepticus can occur during the acute phase, often leading to severe neurological sequelae. Brain imaging ranges from normal to diffuse edema, focal changes, and abnormal signals in the white matter, basal ganglia, and hippocampi. Here, we describe a boy who presented with an acute onset of transient alteration of behavior, meningeal irritation, fever, vomiting, and leg pain. Meningoencephalitis due to M. pneumoniae infection was confirmed by focal pneumonia, positive immunological tests, and increased protein content in cerebrospinal fluid. Magnetic resonance imaging of the brain showed bilateral focal abnormalities in the temporoinsular cortex, and electroencephalographic recordings showed slow waves in the same regions. After early infusion of acyclovir on the first day, aggressive combination therapy with oral erythromycin, and intravenous methylprednisolone and immunoglobulin was promptly initiated once a complete diagnosis was obtained on the second day, and the boy recovered within a few days. Two weeks later, brain imaging findings had resolved completely. The rapid clinical and neuroradiological recovery after immunosuppressive therapy suggests an immune-mediated pathogenetic mechanism. He developed immune-mediated myositis 2 years later demonstrating the instability of his immunological status.
Keywords: encephalitis; immunosuppression; MRI; Mycoplasma pneumoniae